Different scoring methods and psychometric properties of some ability-based emotional intelligence (EI) tests - Marjanović, Iva (Array, 2006)
So far research of emotional intelligence supports the assumption of this concept as a set of mental abilities that can be measured through objective performance-based tests. Such approach demonstrates unsolved problems of correct answers in emotional intelligence tests and scoring related issues. The aim of this research is to examine the influence of different scoring methods of participants’ performance on some psychometric properties of objective emotional intelligence tests. The applied tests were developed under an ability-based model of emotional intelligence (Mayer and Salovey, 1997, 2002). Those tests are intended for assessment of abilities to understand and to manage emotions. 286 university students attending Faculty of Philosophy and the Faculty of Mechanical Engineering and Naval Architecture participated in this research. Various differential scoring methods were used for the participants’ performance assessment. The paper discusses changes in reliability and validity estimations of measures of abilities to understand and abilities to manage emotions. The research findings indicate significant increases in test reliability and to the lesser extent criterion validity indices due to differential weighting of participants’ answers.